1997
DOI: 10.1007/pl00005098
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue induces ongoing activity in rat cutaneous primary afferents and depolarization of DRG neurons via a photosensitive mechanism

Abstract: The dye methylene blue is known as a blocker of guanylyl cyclase and it has been widely used to deplete cells of internal cyclic GMP. The data presented demonstrate an activation of adult rat sensory neurons by methylene blue via a photosensitive mechanism. In single fiber recordings from primary afferents of the rat skin in vitro, methylene blue, applied to the receptive field, induced discharge activity: 2/2 A beta-, 2/4 A delta- and 5/7 C-fibers showed significantly enhanced firing upon 10 microM methylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Depolarizing effects of MB on neuronal structures have been demonstrated in several earlier studies (Burmistrov et al, 1967; Nozdrachev et al, 1984; Nemeth et al, 1985; Kress et al, 1997). Inhibition of Ca 2+ -activated K + channels (Nemeth et al, 1985), activation of Ca 2+ channels (Saitow and Nakaoka, 1997), and facilitation of Na + channel inactivation (Oxford, 1977; Kress et al, 1997) are suggested to be possible mechanisms for MB-induced depolarizations. It appears that the actions of MB, reported in the majority of these studies, are not mediated by the cGMP pathway.…”
Section: Molecular Targets Of Methylene Bluementioning
confidence: 60%
See 2 more Smart Citations
“…Depolarizing effects of MB on neuronal structures have been demonstrated in several earlier studies (Burmistrov et al, 1967; Nozdrachev et al, 1984; Nemeth et al, 1985; Kress et al, 1997). Inhibition of Ca 2+ -activated K + channels (Nemeth et al, 1985), activation of Ca 2+ channels (Saitow and Nakaoka, 1997), and facilitation of Na + channel inactivation (Oxford, 1977; Kress et al, 1997) are suggested to be possible mechanisms for MB-induced depolarizations. It appears that the actions of MB, reported in the majority of these studies, are not mediated by the cGMP pathway.…”
Section: Molecular Targets Of Methylene Bluementioning
confidence: 60%
“…In addition, the functions of voltage-sensitive Na + (Oxford, 1977; Starkus et al, 1984; 1993; Kress et al, 1997), Ca 2+ (Thuneberg, 1990) and Ca 2+ -activated K + channels (Nemeth et al, 1985; Stockand and Samson, 1996; Saitow and Nakaoka, 1997) are also modulated by MB. As a result of MB actions on ion channels, excitability of neurons is altered significantly.…”
Section: Molecular Targets Of Methylene Bluementioning
confidence: 99%
See 1 more Smart Citation
“…8 It seems unlikely that afferent innervation is lacking in the extremities or, if present, without influence on cardiovascular autonomic nerve function under the mentioned physiological conditions. It is known from other investigations that afferent nerve fibers from skin 9 and other organs can be electrophysiologi-cally characterized as C-fibers 10 that, in addition, were often observed to be peptidergic secreting substances like substance P (SP) and calcitonin gene-related peptide (CGRP). 11,12 Again, little is known about perivascular innervation of vessels relevant in hypertension.…”
mentioning
confidence: 99%
“…This immediate pain is caused by stimulation of the epidermal receptors (polymodal nociceptors) which lie at the free ends of the fast A␦ and the slow C-fibers [12]. In detail, it is thought to be an activation of the TRPV1 (transient receptor potential vanilloid 1) receptor that controls heat sensation [13]. A second type of pain, a mediator-induced pain, is caused by the binding of prostaglandins and bradykinin to peripheral pain receptors (EP 2 and B 2 ).…”
mentioning
confidence: 99%